2022
DOI: 10.1039/d1fo03360c
|View full text |Cite
|
Sign up to set email alerts
|

Live Lactobacillus acidophilus alleviates ulcerative colitis via the SCFAs/mitophagy/NLRP3 inflammasome axis

Abstract: The live Lactobacillus acidophilus (La) alleviated colitis by ameliorating intestinal barrier and suppressing inflammation. SCFAs modulated and enriched by La promoted the mitophagy/NLRP3 inflammasome pathway, which helped to improve gut functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 46 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…Among the various factors, the role of gut microbiota has received much attention 18 . Moreover, considerable evidence indicates that probiotics administration could attenuate UC-associated symptoms and inflammation, presumably through modulating the gut microbiota (Table 1) [19][20][21][22][23][24][25][26][27][28][29][30][31][32] . Meanwhile, emerging studies also reported that postbiotic application could reduce the risk of development of UC 31,[33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the various factors, the role of gut microbiota has received much attention 18 . Moreover, considerable evidence indicates that probiotics administration could attenuate UC-associated symptoms and inflammation, presumably through modulating the gut microbiota (Table 1) [19][20][21][22][23][24][25][26][27][28][29][30][31][32] . Meanwhile, emerging studies also reported that postbiotic application could reduce the risk of development of UC 31,[33][34][35][36] .…”
Section: Introductionmentioning
confidence: 99%
“…Although Lactobacillus cannot directly produce SCFAs, its metabolite lactic acid can be utilized by bacteria of all kinds, such as Clostridium propionicum, Propionibacterium, and many other bacteria to ferment acetic acid and propanoic acids (Li, Chen, et al, 2022;Sato et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…By lowering proinflammatory cytokine levels and regenerating intestinal epithelial cells, SCFAs have ameliorated colitis (Banskota et al., 2021; Parada Venegas et al., 2019). Although Lactobacillus cannot directly produce SCFAs, its metabolite lactic acid can be utilized by bacteria of all kinds, such as Clostridium propionicum, Propionibacterium , and many other bacteria to ferment acetic acid and propanoic acids (Li, Chen, et al., 2022; Sato et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…46 Emerging evidence highlights the pivotal role of gut microbiome-derived SCFAs in several diseases, such as diabetes, colitis, allergy, and asthma. [47][48][49][50] Moreover, SCFAs play a significant role in enhancing regulatory T cells and promoting oral tolerance. These mechanisms are likely to contribute to the resolution of food allergies.…”
Section: Papermentioning
confidence: 99%